2019
DOI: 10.1111/fwb.13455
|View full text |Cite
|
Sign up to set email alerts
|

Beavers alter stream macroinvertebrate communities in north‐eastern Utah

Abstract: 1. Understanding changes in macroinvertebrate communities is important because they play a large role in stream ecosystem functioning, and they are an important food resource for fish. Beaver-induced changes to stream morphology could alter macroinvertebrate communities, which in turn could affect food webs and ecosystem function. However, studies investigating the effects of North American beaver activities on macroinvertebrates are rare in the inter-mountain west, an area with high potential for beaver-assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 67 publications
1
16
0
1
Order By: Relevance
“…The occurrence of typically rheophilic species at sites with flowing water (group UNS and particularly FSB) and stagnophilic species in ponds seems critical in terms of biodiversity throughout the catchment (Washko et al, 2020). The engineering activities of beavers usually increase taxonomic diversity at the landscape scale (Anderson et al, 2015;Bylak & Kukuła, 2018;Bylak et al, 2014;Clifford et al, 1993;Hood & Larson, 2014;Robinson et al, 2020;Washko et al, 2020). In the present study, the emergence of new habitats, namely ponds, resulted in increased in faunistic diversity at the stream scale.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…The occurrence of typically rheophilic species at sites with flowing water (group UNS and particularly FSB) and stagnophilic species in ponds seems critical in terms of biodiversity throughout the catchment (Washko et al, 2020). The engineering activities of beavers usually increase taxonomic diversity at the landscape scale (Anderson et al, 2015;Bylak & Kukuła, 2018;Bylak et al, 2014;Clifford et al, 1993;Hood & Larson, 2014;Robinson et al, 2020;Washko et al, 2020). In the present study, the emergence of new habitats, namely ponds, resulted in increased in faunistic diversity at the stream scale.…”
Section: Discussionmentioning
confidence: 57%
“…The taxa that influenced the Sim in invertebrate fauna of sites from the ponds the most were Oligochaeta and Chironomidae based on their abundance. The dominance of Chironomidae and Oligochaeta in beaver pond complexes has been reported in numerous other streams occupied by beavers and was the primary factor distinguishing ponds from flowing sections (Margolis et al, 2001; McDowell & Naiman, 1986; Naiman et al, 1984; Pliūraitė & Kesminas, 2012; Washko et al, 2020). In the present study, Chironomidae were also relatively abundant in flowing sections, although their density was considerably lower in the flowing sections than in most of the beaver ponds.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…25,000 km 2 of new aquatic pond habitat and 550,000 km of riparian interface have been created in boreal and temperate zones (Whitfield et al 2015). Beavers have been proposed as a tool for biodiversity conservation (Law et al 2019;Nummi and Holopainen 2020), and several studies have shown that beavercreated succession can affect aquatic invertebrates in a beaver-modified landscape at a general level (Bush et al 2019;Washko et al 2020). One of the first studies to focus on a specific taxon of aquatic invertebrates found a difference in water beetle abundance in beaver wetlands and non-beaver wetlands (Willby et al 2018).…”
Section: Introductionmentioning
confidence: 99%